Water Security, The Nexus Of Water, Food, Population Growth and Energy - E. A. McBean (The Global Environmental Engineers, 2016)
Issues causing increased water stress and availability throughout the world are complex. The importance of supply-side issues arising from increasing urbanization, causing localized levels of water stress, is described. Further, while the world population has doubled over the last 50 years, water use has tripled. Water use rates have increased (from 400km3 per year per billion people in 1965, to the current level of 600km3 per year per billion people in 2015), as a result of population growth with its associated food and energy implications, and dietary shifts of populations. Water demands in 2025 are projected to be 1500km3 per year, or 60% more than volumes in 2015. The findings in a case study in the Zambezi River basin indicate that while climate change is projected as 25% of the projected impact to future water security issues, 75% of water security issues are attributable to population increases (and its related food, energy, and changing dietary habits) and hence, population increases represent a greater threat to water security.